A case study on the perceptions of I.T. professionals during the transition from a traditional to an agile process model - Machado, Thales de Souza; Ximenes, Yule Trannin; Neves, Vânia de Oliveira; Salgado, Luciana Cardoso de Castro (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
This paper aims to identify and analyze which individual perceptions (behavior, feelings, difficulties, among others) are more frequent in the transition process between traditional and agile methods in the context of software development in a large company. The motivation for this work is due to the observation of the growing adoption of agile work models by large companies and the human aspects involved in this scenario. Thus, the particularity of this research is to offer a perspective focused on the individual aspect of each person involved in the process, allowing the ideas and feelings formed through individual perceptions to be identified and analyzed. This objective is achieved through the qualitative analysis of the speech of four professionals in the I.T. area of a large company in relation to their perceptions about a transition from a traditional development model to an agile development model. To survey the interview questions, the GQM method was used and an analysis of the collected data was carried out according to procedures of the Grounded Theory method, aiming to identify emerging topics among the views exposed by the interviewees. Thus, the following topics were highlighted in the context of the transition: perceived benefits for the team, difficulties faced and solutions to these difficulties.